2017
DOI: 10.1161/circresaha.117.309715
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota in Cardiovascular Health and Disease

Abstract: Significant interest in recent years has focused on gut microbiota-host interaction because accumulating evidence has revealed that intestinal microbiota play an important role in human health and disease, including cardiovascular diseases. Changes in the composition of gut microbiota associated with disease, referred to as dysbiosis, have been linked to pathologies such as atherosclerosis, hypertension, heart failure, chronic kidney disease, obesity and type 2 diabetes mellitus. In addition to alterations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
1,006
2
31

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,253 publications
(1,049 citation statements)
references
References 198 publications
(226 reference statements)
10
1,006
2
31
Order By: Relevance
“…The identification of TMAO as a CVD‐relevant biomarker is a notable example of a disease‐relevant microbial metabolite discovery. By using an untargeted metabolomic approach, Hazen et al identified dozens of metabolites, including choline, TMA, and TMAO – which were significantly different in the cases of CVD compared with age‐ and gender‐matched controls – and confirmed their observations by using several validation cohorts . They then proved that the identified metabolites are from a gut microbiota‐dependent pathway by using traceable isotope‐labeled compounds in animal studies and by establishing the causal role of TMAO in atherogenesis and thrombosis in animal and cell models.…”
Section: Discovery Of Gut Microbiota‐specific Bioactive Metabolitesmentioning
confidence: 89%
See 2 more Smart Citations
“…The identification of TMAO as a CVD‐relevant biomarker is a notable example of a disease‐relevant microbial metabolite discovery. By using an untargeted metabolomic approach, Hazen et al identified dozens of metabolites, including choline, TMA, and TMAO – which were significantly different in the cases of CVD compared with age‐ and gender‐matched controls – and confirmed their observations by using several validation cohorts . They then proved that the identified metabolites are from a gut microbiota‐dependent pathway by using traceable isotope‐labeled compounds in animal studies and by establishing the causal role of TMAO in atherogenesis and thrombosis in animal and cell models.…”
Section: Discovery Of Gut Microbiota‐specific Bioactive Metabolitesmentioning
confidence: 89%
“…However, these nutrients can be utilized by microbes in the gut to produce trimethylamine (TMA) as a byproduct. The TMA absorbed from the gut is then oxidized into TMAO in the liver and has proven to be a strong risk factor for cardiovascular disease (CVD) . The amino acids ingested from dietary intake were generally regarded as materials for our body to synthesize enzymes and proteins, but they can be metabolized earlier by the gut microbes before their absorption into the gut.…”
Section: Microbial Metabolites Are Messengers In the Gut–systemic Aximentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the intestinal bacteria contribute to host health by providing macro-and micro nutrients such as simple carbohydrates e.g. lactose (the core of the HMOS), amino acids, and vitamins; the inhibition of pathogens by competitive exclusion; maintenance of gut immune function; maintenance of normal gut motility; and the prevention of cancer and cardiovascular disease (Brennan and Garrett 2016, Honda and Littman 2016, Kamada et al 2013, Quigley 2011, Rowland et al 2018, Tang et al 2017. On the other hand, an aberrant gut microbiota is associated with diseases including cardiovascular diseases, metabolic syndrome, non-alcoholic fatty liver diseases, obesity, type 2 diabetes, and inflammatory bowel diseases (de Vos and de Vos 2012).…”
Section: Comparative Genomics Reveal Thatmentioning
confidence: 99%
“…Adicionalmente, a maior exposição à alérgenos contribui para a polarização da resposta imunológica para o tipo Th2, causando uma desregulação no balanço homeostático Th1/Th2, aumentando assim a probabilidade do desenvolvimento de doenças alérgicas (Sult et al, 2003;Eder, Ege and von Mutius, 2006). Em adição a essa hipótese, muitos estudos vêm demonstrando que o desequilíbrio da interação microbiota--hospedeiro aumenta a suscetibilidade à diversas doenças como a artrite (Taneja, 2014), esclerose múltipla (Bhargava and Mowry, 2014), aterosclerose (Org, Mehrabian and Lusis, 2015), infecções intestinais (Ross, Spinler and Savidge, 2016), doenças cardiovasculares (Tang, Kitai and Hazen, 2017), diabetes mellitus (Tai, Wong and Wen, 2015) e as doenças alérgicas (Gigante et al, 2011;Herbst et al, 2011;Kang, Cai and Zhang, 2016;Losses and Larger, 2016).…”
Section: Asmaunclassified